Two degree of freedom internal model control-PID design for LFC of power systems via logarithmic approximations. (January 2018) - Singh, Jay; Chattterjee, Kalyan; Vishwakarma, C.B.
Abstract: Load frequency controller has been designed for reduced order model of single area and two-area reheat hydro-thermal power system through internal model control – proportional integral derivative (IMC-PID) control techniques. The controller design method is based on two degree of freedom (2DOF) internal model control which combines with model order reduction technique. Here, in spite of taking full order system model a reduced order model has been considered for 2DOF-IMC-PID design and the designed controller is directly applied to full order system model. The Logarithmic based model order reduction technique is proposed to reduce the single and two-area high order power systems for the application of controller design.The proposed IMC-PID design of reduced order model achieves good dynamic response and robustness against load disturbance with the original high order system. Highlights: A reduction technique has been proposed to reduce the nth high order complex power system into kth-order reduced models.. Load frequency controllers (LFC) have been designed for the reduced models of reheat hydro thermal power systems. For LFC, a two degree of freedom internal model control (TDF IMC) proportional integral derivative (PID) has been designed. A random step load and variable load have been applied in the system to check the robustness of proposed LFC.